Evaluation of prophylaxis treatment of Candida in alaryngeal patients with tracheoesophageal voice prostheses. (24th November 2014) - Messing, Barbara P.; Kim, Melissa; Hirata, Richard; Thompson, Carol B.; Gebhart, Samantha; Sugar, Elizabeth A.; Saunders, John M.; Sciubba, James; Califano, Joseph A.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The objective of this study was to evaluate the effectiveness of nystatin and Biotène® mouthwash Oral Rinse for controlling Candida in total laryngectomy (TL) patients with a tracheosophageal voice prosthesis (TEP) because Biotène® mouthwash Oral Rinse is a less costly alternative to nystatin and requires less adherence time. Study Design Randomized, unblinded, crossover trial. Methods Twenty‐one TL patients were randomized to receive nystatin followed by Biotène® mouthwash Oral Rinse, or the reverse order, after a basic oral‐care phase (i.e., brushing teeth, cleaning dentures). A Provox® 2, 22.5 French TEP, which is an indwelling silicone voice prosthesis, was placed at the beginning of each phase. Patients were provided with oral care instructions at randomization and medication‐specific instructions with each treatment's initiation. TEPs were processed and evaluated for Candida growth as colony‐forming units (CFUs). Wilcoxon signed‐rank tests were used for comparisons between treatments. Results Fifteen patients were available for comparisons of Candida counts (6 received nystatin; 9 received Biotène® mouthwash first). Overall, the median log10 (CFUs) remained high regardless of treatment (no medication: 8.9; nystatin: 8.7; Biotène® mouthwash: 8.4). However, the median counts for both nystatin and Biotène® mouthwash Oral Rinse were lower than those for no medication (difference [Δ]:−0.9 and −0.3, respectively), although only nystatin was significantly lower (P = 0.02). There was no significant difference between the two treatments (P = 0.22). Overall, median medication‐adherence was high (97%), and Biotène® mouthwash adherence was significantly higher than that of nystatin (Δ: 7.6%; P = 0.03). Conclusion Nystatin and Biotène® mouthwash Oral Rinse had similar CFU levels, with nystatin showing a significant improvement over usual oral care. Biotène® mouthwash is a less costly alternative to nystatin, with a less complex treatment protocol that might make it preferable to patients and clinicians. Level of Evidence 1b Laryngoscope, 125:1118–1123, 2015